2016
DOI: 10.1063/1.4939938
|View full text |Cite
|
Sign up to set email alerts
|

Electronic states in spherical GaN nanocrystals embedded in various dielectric matrices: The k ⋅ p-calculations

Abstract: Using the envelope-function approximation, the single-particle states of electrons and holes in spherical GaN nanocrystals embedded in different amorphous dielectric matrices (SiO2, Al2O3, HfO2 and Si3N4) have been calculated. Ground state energies of electrons and holes in GaN nanocrystals are determined using the isotropic approximation of the k ⋅ p -Hamiltonian. All the ground state energies are found to increase with lowering the nanocrystal size and are proportional to the R−n, where R is the nanocrystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…What makes this model easy to choose is determined by several advantages such as the overall simplicity compared to other computational tools, while including all complexities such as the periodicity of the crystal, strain [19] in addition to the effect of remote bands in the effective mass tensor. However the (EFA) method has also some limitations, as it is applicable only to nanocrystals with radii more than approximately 1 nm [20], while author in Ref. [21] concluded that even though (EFA) is not perfectly accurate, it can be very useful from the conceptual point of view and often provides valuable physical insight.…”
Section: Introductionmentioning
confidence: 99%
“…What makes this model easy to choose is determined by several advantages such as the overall simplicity compared to other computational tools, while including all complexities such as the periodicity of the crystal, strain [19] in addition to the effect of remote bands in the effective mass tensor. However the (EFA) method has also some limitations, as it is applicable only to nanocrystals with radii more than approximately 1 nm [20], while author in Ref. [21] concluded that even though (EFA) is not perfectly accurate, it can be very useful from the conceptual point of view and often provides valuable physical insight.…”
Section: Introductionmentioning
confidence: 99%